Managing the Issues in the Textile Industry Using Improved Electro-Spinning Technique (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Since ancient times natural fibers and textiles have been used by people. Our ancestors used fur and animal skin to dress to shield them from the climate, but soon they began to produce primitive garments using vegetable fibers. The processing of fabrics is made more available and inexpensive with the advent of machines. This industrial revolution turned the idea of textile manufacture into a true industry. Today, there is a modern innovation on the textile field that can add unique functions and functionality to the materials through the creation of new technology. In this paper, we are using the electro-spinning to use nanoparticles in the textile industry as synthetic fibers, which can be used to solve the typical issues such as fiber growth of microorganisms, ultraviolent radiation robustness, and so on. Furthermore, it is also analysed how nanoparticles are embedded in special ultra-thin fibers.